Using biomass of heterotrophic marine microalga Schizochytrium for improving docosahexaenoic acid (DHA, C22:6-3) in chicken eggs - Anh, Hoàng Thị Lan; Quỳnh, Hoàng Thị Hương; Việt, Trần Quốc; Hồng, Nguyễn Thị; Huyền, Ninh Thị; Hồng, Đặng Diễm (Vietnam Journal of Biotechnology, 2016)
The consumers’ demand for food products of superior health quality are growing. Many researches have been conducted to enhance nutritional value of foods as meat, eggs, and milk. Eggs are considered the most convenient way to supply bioactive nutrients. While protein and total lipid concentrations of eggs are not readity altered, fatty acid composition, mineral and vitamin contents can be modified by feeding the hens with certain dietary ingredients. In this study, we investigated the effect of adding microalga Schizochytrium mangrovei PQ6 biomass in basal diet on egg production and egg quality parameters, especially docosahexaenoic acid content (DHA, C22:6w-3) of laying hens. Total number of 60 line G3 laying hens (mix between line HA and Hungary, 51-60 weeks of age) were randomly allotted into one of three groups by 20 hens each (KPCS, KP1 and KP2). All groups of hens were fed basal diets of standard ingredients while feed of KP1 and KP2 group of hens was supplemented with S. mangrovei PQ6 biomass as a source of w-3 fatty acid in amount of 1 and 5 % respectively. The obtained results have shown that, after trial 10 weeks, addional microalgal biomass in the diet of hens did not effect on egg production and normal egg quality parameters (egg weight, ratio of yolk and albumen, Haugh unit, yolk color). However, adding 5% microalga biomass in diet improved markedly DHA content in egg (reached up to 234.19 mg/egg) compared to that in control (52.85 mg/egg) and 1% level of microalgal biomass in basal diet (54.15 mg/egg).